PROS (Promoting Researchers Online Supervision) Project: The ViPER (Virtual Project Environment for Research) Taxonomy and Needs Analysis Study - Basiel, Anthony 'Skip' (Proceedings of the International Conference on Networked Learning, 2002)
The PROS (Promoting Researchers Online Supervision) project aims to provide the necessary resources and tools to support the online supervision process for projects and research. One of the objectives is to develop a mediation tool to aid the instructional designer and the subject matter expert during the conversion process of traditional face-to-face teaching to web-based delivery and collaboration. Another objective is to take an evidence-based approach in the design process of the Virtual Project Environment for Research (ViPER) by conducting a needs analysis and usability study. E-learning projects are commonly done based upon previously conducted research or worse, with no measurement of the learner's needs at all. This paper addresses that particular gap in the research process. Details of the needs analysis and usability study conducted with this project are also presented. This paper offers the Virtual Project Environment for Research (ViPER) taxonomy as a focus of discussion. A 'taxonomy' is a scheme of classification or, in this study, a matrix that is defined as a situation that aids a person (or society) grow and develop. This document argues that the ViPER taxonomy supports the online learning and development process. As applied to this study, the definition of an educational taxonomy can be refined to: 'A general sequence in the growth of the structural complexity of many concepts and skills that may be used to guide the formulation of specific targets or the assessment of specific outcomes.' Several topics are discussed leading to the design of the taxonomy. The presentation of the taxonomy is developed into a three-dimensional (3D) model. Two examples are offered: a real world paper-based tool and an online 'navihedron'. An interactive Javascript form is used to input the taxonomy data producing a graphical guideline for the instructional designer as to the appropriate online tools to use in supporting the learning process. (http://www.iclml.mdx.ac.uk/research/viper/ViPERprofile.HTM ) Expert review will be the evaluation method used to assess the taxonomy. Online pedagogical academics will be interviewed and surveyed to gauge the value of the research as well as live events such as the NLC'02 conference. Web-constuctivism, the adaptation of Constructivist learning principles to a web-basedVLE, and the Transitional Autonomy Model (TAM) are the supporting theories for this study supported also by the Transactional Distance Theory (Moore, M 1993).